2008
DOI: 10.1007/s10463-008-0213-1
|View full text |Cite
|
Sign up to set email alerts
|

Explicit estimators under m-dependence for a multivariate normal distribution

Abstract: The problem of estimating parameters of a multivariate normal p-dimensional random vector is considered for a banded covariance structure reflecting m-dependence. A simple non-iterative estimation procedure is suggested which gives an explicit, unbiased and consistent estimator of the mean and an explicit and consistent estimator of the covariance matrix for arbitrary p and m.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Some properties of the estimators where given in [12], where it was shown that the estimatorΣ (1) (p) = (σ ij ) given in Proposition 2.1 is consistent. But, the estimator for the covariance matrix above lacks the property of unbiasedness.…”
Section: Previous Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Some properties of the estimators where given in [12], where it was shown that the estimatorΣ (1) (p) = (σ ij ) given in Proposition 2.1 is consistent. But, the estimator for the covariance matrix above lacks the property of unbiasedness.…”
Section: Previous Resultsmentioning
confidence: 99%
“…In [12] an explicit estimator for the covariance matrix for a multivariate normal distribution when the covariance matrix have an m-dependence structure is presented. Ohlson et al [12] propose estimators for the general case when m + 1 < p < n and establish some properties of it.…”
Section: Explicit Estimators Of a Banded Covariance Matrixmentioning
confidence: 99%
See 3 more Smart Citations